The Ripple Effect : Influence of Exchange Rate Volatility on Indian Sectoral Indices - Mohapatra, Amiya Kumar; Mohanty, Debasis; Sardana, Varda; Shrivastava, Amit (Indian Journal of Finance, 2024)
Purpose : The study aimed to analyze the spillover effect of foreign exchange rate volatility on the sectoral indices of India. The paper included five exchange rates (USD-INR, EURO-INR, GBP-INR, CNY-INR, and JPY-INR) and seven (automobile, banking, energy, FMCG, infrastructure, information & technology, and pharmaceutical) sectoral indices in this study. Methodology : The study used the generalized autoregressive conditional heteroscedasticity (GARCH) (1,1) model for modeling volatility. T-GARCH model was used to estimate the leverage effect; and DCC-GARCH was used for analyzing the spillover effect of exchange rates on select sectoral indices. Findings : The study found that leverage effect existed in all the series as the sum of α and λ of T-GARCH is less than 1, and the model was found acceptable. In the long-run, there was a spillover effect from all the exchange rates to all the sectoral indices. A short-run USD-INR spillover was observed on five sector indices, excluding banks and infrastructure. For every sectoral index, the DCC α of EURO-INR was determined to be negligible. Therefore, there was no transmission of short-term volatility from the EURO-INR to sectoral indices. Indexes of the FMCG, infrastructure, and IT sectors were not affected by the short-term volatility of the GBP-INR. DCC α and DCC β of CNY-INR were found to be significant for all the indices, which revealed transmission of information in the short-run as well as in the long-run. The three indices for which DCC α of JPY-INR was found insignificant are the bank, FMCG, and pharma sectors. Implications : The results of this study shall aid policymakers and regulators in formulating investor-friendly rules and regulations to maintain a steady stock market. Prospective stakeholders shall also benefit from this research by using it to make reliable and well-informed investment decisions and portfolios. This study could be used as a reference document in other research and academic discussions as well. Originality : Foreign exchange rates and sectoral indices, the focus of this study, have received relatively little attention in the literature despite the fact that research on stock markets has gained a lot of attention recently. This research will be a trailblazer in examining how fluctuations in foreign exchange rates impact India’s sectoral indexes.